Constructing Odd-Variable Rotation Symmetric Boolean Functions With Optimal AI and Higher Nonlinearity - Yindong Chen (IEEE Access, 2019)
As a part of the field of cryptography, rotation symmetric Boolean functions have rich cryptographic significance. In this paper, based on the knowledge of integer compositions, we present a new construction of odd-variable rotation symmetric Boolean functions with optimal algebraic immunity. The nonlinearity of the new rotation symmetric Boolean functions is much better than that of the previously ones with optimal algebraic immunity. And the algebraic degree of the function class is also much high. Moreover, it is shown that our new functions have almost optimal fast algebraic immunity within the range of variable numbers that ordinary computers can calculate.